Techno-Economic Assessment and Sensitivity Analysis of Electricity Generation from Wind Energy in a Low-Wind-Speed Region of Egypt - Abdelhady, Suzan (Global Journal of Energy Technology Research Updates, 2024)
This study conducts a detailed techno-economic evaluation and sensitivity analysis of wind energy generation in Egypt’s Fayoum Governorate, a region characterized by low wind speeds. It represents the first investigation of wind energy potential encompassing four key locations within the governorate: Qarun Lake, Rayan Valley, Kom Ushim, and Fayoum City. Statistical analysis of long-term wind data, based on the Weibull distribution, shows a consistent average wind speed of 6.02 m/s at a 50-meter hub height across all sites. Eight small- to medium-scale wind turbines were assessed for their annual energy output, capacity factor, and Levelized Cost of Electricity (LCOE) using the System Advisor Model (SAM). Among these, the Endurance E3120 50 kW turbine emerged as the most cost-effective, with the lowest LCOE of 4.85 ¢/kWh and the highest capacity factor. The sensitivity analysis identified capital cost as the dominant factor influencing LCOE, followed by the fixed charge rate. Overall, the findings confirm the technical and economic viability of small wind turbine deployment in low-wind-speed inland areas, encouraging broader adoption of decentralized renewable energy solutions in Egypt.